Fossil Fuel Divestment Strategies: Financial and Carbon-Related Consequences. (March 2019) - Hunt, Chelsie; Weber, Olaf
Fossil fuel divestment is discussed controversially with regard to its financial consequences and its effect on decarbonizing the economy. Theory and empirical studies suggest arguments for both financial underperformance and outperformance of divestment. Therefore, our first research objective is to understand the financial effect of divestment. The second objective is to analyze the influence of divestment strategies on the carbon intensity of portfolios. Empirically, our analysis is based on the Canadian stock index TSX 260 for the time between 2011 and 2015. The results of the study suggest higher risk-adjusted returns and lower carbon intensity of the divestment strategies compared with the benchmark. We conclude that divestment is not only an ethical investment approach but also that it is able to address financial risks caused by climate change and, at the same time, is able to reduce the carbon exposure of investment portfolios.